Local and Global Risk Factors for the Development of Bulgaria and the World in the Second Decade of the 21st Century (UNWE Yearbook, 2016)
The study considers the risks for Bulgaria that are the result of the bad practices of the ruling class to „accelerate“ the processes of concentration and centralisation of capital through the destabilization and destruction of the nation. These risks are considered with reference to the phase from Kuznets generation cycle in which the Bulgarian economy is at the moment as well as the increased probability for ravage of the present new working generation. The global risks are mostly connected with the specifics of the development of the world economy and the processes of translocation of the world trade hub from the USA to China in particular; with the increasing vassalage of the European and, in particular, the Bulgarian political elite from the American Anglo-Saxon and American Jewish elites. The overlay of local and global risks during the second decade of the 21st century is considered as well.